Taâ€™wÄ«l Teologis AbÅ« Maná¹£Å«r Al-MÄturÄ«dÄ« (Pembacaan Kritis atas Ayat-ayat Keesaan Tuhan) - Izzatu Tazkiyah (Religia, 2018)
Historically, the discourse of exegesis and taâ€™wÄ«l does not always go hand in hand. This was the case, especially when the al-Asyâ€™ÄrÄ« school of thought was in power. In this era, the exegesis had been positioned superior to the taâ€™wÄ«l whose existence was not only regarded as the Islamic opposition but also the deviation of the truth. In this study, the author attempts to unveil the theological taâ€™wÄ«l of al-MÄturÄ«dÄ« on his magnum opus Taâ€™wÄ«lat Ahl al-Sunnah and Kitab al-Tawhid. By considering its capability of reconciling traditionalists (Ash'ariyah) with rationalists (Muktazilah), the magnum opus of al-Maturidiâ€™s becomes a research object of the current study. In particular, this study investigates the research object by means of comparative theological and exegesis approaches, with three main findings. The first finding shows that the concept of taâ€™wÄ«l constructed by al-MÄturÄ«dÄ« in his general exegesis seems very loose. The second finding demonstrates that the objectivity of the meaning presented by al-MÄturÄ«dÄ« sometimes reduces due to its theological views which appear subjective. The third finding reveals a contradiction. On one side, al-Maturidiâ€™s theological view can assuage any ideas that clash with Islam. On another side, however, al-MÄturÄ«dÄ« tried to base the doctrine of Sunni theology.